2015
DOI: 10.1016/j.cossms.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

How do energetic ions damage metallic surfaces?

Abstract: Surface modification of structural and functional materials under bombardment by energetic ions is observed under different conditions in and can be either an unavoidable effect of the irradiation or an intentional modification to enhance materials properties. Understanding the basic mechanisms is necessary for predicting property changes. The mechanisms activated during ion irradiation are of atomic scale and atomic scale modeling is the most suitable tool to study these processes. In this paper, we present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…12 Likewise, the interactions of these shockwaves with a free surface can lead to the surface roughening and creation of huge vacancy dislocation loops. 15,16 In the 0.25-ps snapshot, one can see that the sonic wave propagates without creating low-density regions. For this reason, the supersonic regime is often considered destructive, whereas the sonic regime is considered non-destructive.…”
Section: Resultsmentioning
confidence: 99%
“…12 Likewise, the interactions of these shockwaves with a free surface can lead to the surface roughening and creation of huge vacancy dislocation loops. 15,16 In the 0.25-ps snapshot, one can see that the sonic wave propagates without creating low-density regions. For this reason, the supersonic regime is often considered destructive, whereas the sonic regime is considered non-destructive.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments on Xe + ion irradiation of In, Ag, Pb, Au showed that the number of craters per ion increases with an increase in the material density [1]. Dislocation loops in the irradiated metals are observed in experiments [2][3][4] and computer simulations [5,6]. For example, a greater number of loops was indicated in the thick iron sample, as compared to the bulk material, irradiated with Fe+ ions of energy 500 keV [2].…”
Section: Introductionmentioning
confidence: 86%
“…The free surfaces influence not only the number and position of survived point defects, but also the type of the formed damage near the surface. In particular, the formation of craters and dislocation loops in the surface region after the ion irradiation was found in the experimental [1][2][3][4] and theoretical studies [5,6]. Experiments on Xe + ion irradiation of In, Ag, Pb, Au showed that the number of craters per ion increases with an increase in the material density [1].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations